THE MESOZOIC AND CENOZOIC EXHUMATION HISTORY OF TIANSHAN AND COMPARATIVE STUDIES TO THE JUNGGAR AND ALTAI MOUNTAINS - Guo Z.; Zhang Z.; Wu C.; Fang S.; Zhang R. (My University, 2006)
The Tianshan is a Cenozoic intracontinental orogenic belt. To constrain its deformation history during Mesozoic and Cenozoic, we conducted integrated research on apatite fission track dating from different sections across the Tianshan. The fission-track analysis yields 2 episodic rapid cooling events, interpreted as exhumation of rocks because of the uplift of the mountains. The first is about from Late Jurassic to Early Cretaceous, and the second is about from Miocene to the present. We suggest the Cenozoic exhumation marked the uplift of the Tianshan resulting from the India-Asia collision. The Fission-track dating also shows the Tianshan is expanding by thrusting northward and southward while it is uplifting in Cenozoic. The result of the apatite fission track dating from Junggar and Altai mountains is different from those in Tianshan and they only recorded a continuous period of cooling since late Mesozoic. This paper proposes that the widespread Mesozoic denudation of the Tianshan, Junggar and Altai mountains was possibly related to extensional tectonics resulted from the collapse of the Paleozoic Tianshan orogenic belt. The fact that the Cenozoic tectonic activity in Junggar and Altai mountains is not as strong as in Tianshan implies that the Cenozoic intracontinental deformation in Central Asia is propagating northward resulting from the India-Asia collision.
Keywords: APATITE; FISSION TRACK DATING; MESOZOIC AND CENOZOIC; TIANSHAN; UPLIFT; Мезозой::Меловая; Мезозой::Юрская; Кайнозой::Неоген::Миоцен